PENGARUH KESADARAN WAJIB PAJAK, TRANSPARANSI PAJAK DAN PENGGUNAAN APLIKASI E-FILING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA UMKM DI KOTA MANADO - Pawama, Shinta D.; Sondakh, Jullie J.; Warongan, Jessy D. L. (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to analyze and empirically prove the effect of taxpayer awareness, tax transparency, and the use of e-filling applications on individual taxpayer compliance at MSMEs in Manado City. This type of research is quantitative research. The population in this study is the individual taxpayers of SMEs in Manado City as many as 5,184. Sampling using the Slovin formula obtained a sample of 100 respondents. The data collection method used a questionnaire using multiple regression data analysis with the help of SPSS version 22. The results showed that taxpayer awareness (X1) and the use of e-filing applications (X2) had an effect on increasing individual taxpayer compliance on MSMEs in Manado City. Meanwhile, tax transparency (X3) has no effect in increasing individual taxpayer compliance with MSMEs in Manado City.